2013
DOI: 10.1002/macp.201200649
|View full text |Cite
|
Sign up to set email alerts
|

Shape‐Memory Natural Rubber: An Exceptional Material for Strain and Energy Storage

Abstract: Shape‐memory polymers (SMPs) are smart, responsive materials with numerous potential applications. Based on previously introduced shape‐memory natural rubber (SMNR), which shows exceptional properties such as strain storage of 1000%, cold storage, cold programmability, and mechanical and thermal triggers tunable both during and after programming, different SMNRs regarding their shape‐memory parameters are investigated. Furthermore, their energy‐storage capability and their mechanical properties are explored. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 38 publications
4
108
1
1
Order By: Relevance
“…[ 10 ] The set of properties can be greatly enhanced by blending, [11][12][13][14][15] functional groups, [16][17][18] and additives. [ 20,21 ] It was found that whenever NR is vulcanized below a critical degree of crosslinking, it generates crystals upon strain that are stable at room temperature and can thus stabilize a programmed shape. One way to achieve this is to design a material that allows re-arrangement of its microstructure by such an external stimulus, which then stays intact after removing the stimulus.…”
Section: Doi: 101002/adma201305698mentioning
confidence: 99%
“…[ 10 ] The set of properties can be greatly enhanced by blending, [11][12][13][14][15] functional groups, [16][17][18] and additives. [ 20,21 ] It was found that whenever NR is vulcanized below a critical degree of crosslinking, it generates crystals upon strain that are stable at room temperature and can thus stabilize a programmed shape. One way to achieve this is to design a material that allows re-arrangement of its microstructure by such an external stimulus, which then stays intact after removing the stimulus.…”
Section: Doi: 101002/adma201305698mentioning
confidence: 99%
“…After cooling below T trans , the fixed temporary shape can be stored under ambient conditions for a long period of time. [47][48][49][50][51][52] The convenient preparation of temporary shape is usually achieved by directly stretching or compressing the SMPs under ambient conditions through "reversible plasticity shape memory" or strain-induced polymer crystallization. [19] Thermoresponsive SMPs have recently been utilized in fabricating smart, programmable nanooptical components, such as diffraction gratings and optical beam-power splitters.…”
Section: Introductionmentioning
confidence: 99%
“…Tiller and co-workers [18][19][20] described strain-induced crystals in a lightly cross-linked NR served as a temporary network to fix the deformed shape, fulfilling the shape memory performance. The trigger temperature for shape recovery can be increased to room temperature by changing the crosslink density, deformation temperature, and the stressed state of the deformed sample.…”
mentioning
confidence: 98%